Dental responsibility loadings and the relative value of dental services. (22nd May 2017) - Teusner, DN; Ju, X; Brennan, DS
Abstract: Objective: To estimate responsibility loadings for a comprehensive list of dental services, providing a standardized unit of clinical work effort. Methods: Dentists (n = 2500) randomly sampled from the Australian Dental Association membership (2011) were randomly assigned to one of 25 panels. Panels were surveyed by questionnaires eliciting responsibility loadings for eight common dental services (core items) and approximately 12 other items unique to that questionnaire. In total, loadings were elicited for 299 items listed in the Australian Dental Schedule 9th Edition. Data were weighted to reflect the age and sex distribution of the workforce. To assess reliability, regression models assessed differences in core item loadings by panel assignment. Estimated loadings were described by reporting the median and mean. Results: Response rate was 37%. Panel composition did not vary by practitioner characteristics. Core item loadings did not vary by panel assignment. Oral surgery and endodontic service areas had the highest proportion (91%) of services with median loadings ≥1.5, followed by prosthodontics (78%), periodontics (76%), orthodontics (63%), restorative (62%) and diagnostic services (31%). Preventive services had median loadings ≤1.25. Conclusion: Dental responsibility loadings estimated by this study can be applied in the development of relative value scales.